PERTANGGUNGJAWABAN DIREKSI ATAS PERBUATAN MELAWAN HUKUM YANG DILAKUKAN DALAM MENGURUS PERSEROAN TERBATAS - Lorensia Perangin-angin; Bismar Nasution; T. Keizerina Devi Azwar (Universitas Sumatera Utara, 2013)
Limited company, has some components such as RUPS, director and commissioners. Corporate as an Independent legal subject is artificia person, that need the director as a leader. In the same way, a company doesn’t have a function to run their rights and obligations without director’s help. Director’s existence in the company, it’s just like the life in that company. It is impossible for the company, without the director. On the contrary, It is impossible there’s a director without the company. Director’s function is to take care of the company to purpose and objectives of the company in accordance with good ethics and responsibly. Conduct of the research is normative legal research. First step, the normative legal research based on the secondary law materials. For example: an inventory of regulations relating to the civil law analysis in particular against setting regarding liability of Directors for tort commited in taking care of the company. It is also taken from the written materials relating to this issue. Director’s responsibility of tort of law, in taking care of the company is set out in article 97 paragraph (1) and (2) of Act Number 40 of 2007, which stated the board of Director is responsible to manage the company, where the mandatory clearance carried out each member with good ethics and full of responsibility. The directors are given the opportunity to defend himself with the business judgment rule. So, the court is obligated check for those decisions whether the actions of the director is indeed in the interest of the company and with good ethics and attention to minorities shareholder in that company. The director’s responsibility is including their own assets in case they are proven violate the duty of care and duty of loyality. Keywords: Pertanggungjawaban, direksi, perbuatan melawan hukum